GERONTECNOLOGICAL PERSPECTIVE ON QUALITY OF LIFE - Leyla ATEŞOĞLU (Fırat University, 2019)
Along with the increase in the elderly population and the prolongation of the life expectancy, the societies need to be prepared for this development. Maintaining the health and quality of life of an aging society is of social and economic importance. It is emphasized that having a chance to live a longer life compared to the old days will not be meaningful without increasing the quality of life and that the health expectancy is much more important than the life expectancy. In this context, the concept of "Geronteknoloji" is a concept that has been proposed for the design of new products and services for elderly people, which is a combination of gerontology and technology sciences. Increasing use of technology facilitates access to health services for the elderly and increases quality of life. This study was planned and conducted to determine the level of interest in gerontontology of individuals with cardiovascular disorders and the impact of gerontological products on their quality of life. An information form which includes descriptive characteristics of the participants and the World Health Organization Quality of Life Elderly Module (WHOQOL-OLD) to assess the quality of life were used to collect the research data. As a result of the research; It was determined that 91.7% of the participants had never heard the term gerontology before, but 79.2% had confidence in the presence of the device they carried in their bodies. The vast majority of participants view the technology as moderate. Using technology products to remind them of 97.9% of their drug time, the participants think that technology makes daily life easier. More than half of the participants stated that their quality of life was changed in a delightful way, considering that their quality of life was affected in part by positive feedback after the devices they used.